The International Students' Handbook : Living and Studying in Australia - Ong, Danny (Sydney UNSW Press, 2009)
Studying abroad is an appealing prospect but involves a great deal of thought and preparation. The process can be fraught with uncertainties and a lack of knowledge in many areas. This practical book helps you evaluate your options every step of the way
Include Index
Keywords: Australia -- Students, Foreign -- Education, Higher